Novel PSI domains in plant and animal H+-inositol symporters. - Dotzauer, Dorina; Wolfenstetter, Susanne; Eibert, Dorothee; Schneider, Sabine; Dietrich, Petra; Sauer, Norbert (Traffic (Copenhagen, Denmark), 2010)
Inositols are indispensable components of cellular signaling molecules, and impaired cytoplasmic inositol concentrations affect cellular development. Although most cells can synthesize inositol de novo, plasma membrane-localized inositol uptake systems are indispensable for normal development. Here, we present in-depth functional analyses of plasma membrane-localized H(+)-inositol symporters from human and from the higher plant Arabidopsis thaliana. Sequence comparisons, structural and phylogenetic analyses revealed that these transporters possess conserved extracellular loop domains that represent homologs of plexins/semaphorin/integrin (PSI) domains from animal type I receptors. In these receptors, PSI domains modulate intracellular signaling via extracellular protein-protein interactions. Comparisons of H(+)-inositol symporters with wild type, mutated and truncated PSI domains in different expression systems showed that removal of the entire loop domain increased the V(max) of inositol uptake. Finally, we show that the PSI domains are targets for Ni(++) ions that cause a complete loss of transport activity. A possible role of Ni(++)-binding to PSI domains in Ni(++)-induced carcinogenicity is discussed.

Routes to the tonoplast: the sorting of tonoplast transporters in Arabidopsis mesophyll protoplasts. - Wolfenstetter, Susanne; Wirsching, Petra; Dotzauer, Dorina; Schneider, Sabine; Sauer, Norbert (The Plant Cell, 2012)
Vacuoles perform a multitude of functions in plant cells, including the storage of amino acids and sugars. Tonoplast-localized transporters catalyze the import and release of these molecules. The mechanisms determining the targeting of these transporters to the tonoplast are largely unknown. Using the paralogous Arabidopsis thaliana inositol transporters INT1 (tonoplast) and INT4 (plasma membrane), we performed domain swapping and mutational analyses and identified a C-terminal di-leucine motif responsible for the sorting of higher plant INT1-type transporters to the tonoplast in Arabidopsis mesophyll protoplasts. We demonstrate that this motif can reroute other proteins, such as INT4, SUCROSE TRANSPORTER2 (SUC2), or SWEET1, to the tonoplast and that the position of the motif relative to the transmembrane helix is critical. Rerouted INT4 is functionally active in the tonoplast and complements the growth phenotype of an int1 mutant. In Arabidopsis plants defective in the β-subunit of the AP-3 adaptor complex, INT1 is correctly localized to the tonoplast, while sorting of the vacuolar sucrose transporter SUC4 is blocked in cis-Golgi stacks. Moreover, we demonstrate that both INT1 and SUC4 trafficking to the tonoplast is sensitive to brefeldin A. Our data show that plants possess at least two different Golgi-dependent targeting mechanisms for newly synthesized transporters to the tonoplast.